2016
DOI: 10.1007/978-3-319-32213-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Balinese Character Recognition Using Bidirectional LSTM Classifier

Abstract: The character recognition of cursive scripts always be provocative. The inherent challenges exists in cursive scripts captured researcher's interest to crop up the issues that surface in building a reliable OCR. There exists many ancient languages that require state of the art techniques to be applied on them. Every such language has its own inherent complex structure. We proposed Balinese character recognition system by Recurrent Neural Network (RNN) approach, so that their characteristics may get substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
(13 reference statements)
0
6
0
2
Order By: Relevance
“…In [18] a technique for Balinese text segmentation is being proposed that includes pre-processing i.e converting it into grey scale after which text segmentation is done usingLinear Discriminant Array (LDA) algorithm and the accuracy achieved is increased when compared. In technique [19] a method for historical document analysis has been proposed. Firstly, various neural networks are used like CNN, LSTM and RNN, secondly it focuses on word or text image of different length using both one and two dimensional RNN and error rate drops to 0.42.…”
Section: Relatedworkmentioning
confidence: 99%
“…In [18] a technique for Balinese text segmentation is being proposed that includes pre-processing i.e converting it into grey scale after which text segmentation is done usingLinear Discriminant Array (LDA) algorithm and the accuracy achieved is increased when compared. In technique [19] a method for historical document analysis has been proposed. Firstly, various neural networks are used like CNN, LSTM and RNN, secondly it focuses on word or text image of different length using both one and two dimensional RNN and error rate drops to 0.42.…”
Section: Relatedworkmentioning
confidence: 99%
“…The aforementioned complexities are not linguistic specific rather to deal with such challenges make it convenient for correct localization of other cursive text. Therefore in literature, by considering the complexities of relevant script, various techniques have been proposed separately for text localization, extraction and recognition as explained in [6]- [9].…”
Section: A Complexities Relevant To Scene Text Imagesmentioning
confidence: 99%
“…It is suitable for context learning applications. It has been applied on various research tasks in document image analysis specifically relevant to cursive script as reported in [3]- [5] and [9]. The proposed system is investigated by multidimensional LSTM networks because it maintains contextual information and temporarily correlates the new sequences with previous one.…”
Section: B Mdlstm Network Training For Arabic Scene Textmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabic every character appearance depends on the previous character, in this way learning the context of current character is crucial. There are some solutions suggested by recent research to tackle with the variability of characters with context learning approaches as proposed in [9,10,11]. The most prominent context learning approach specifically used for unconstrained cursive text research is Long Short Term Memory (LSTM) networks [4].…”
Section: Introductionmentioning
confidence: 99%